The Influence of Psychological Factors on Consumer Purchasing Decisions in the New Normal Era with Age and Education Level as Moderating Variables - Mei Monika Asri; Roos Kities Andadari (International Journal of Economics Development Research (IJEDR), 2023)
The COVID-19 pandemic has brought significant changes to consumer behavior and the retail industry. As a result, businesses need to understand the impact of psychological factors on consumer purchasing decisions in the "new normal" era. This study focuses on a specific case study of Salon Deskhabeautylash, a beauty salon in Indonesia. This study aims to investigate the impact of consumer psychology factors on purchasing decisions in the "new normal" era, with age and education level as moderating variables. The research design employed in this study is quantitative research, and the population studied consists of individuals who have visited Salon Deskhabeautylash. A sample of 100 individuals was used in this study, and primary data was collected using a survey method with a questionnaire. The data analysis technique employed was multiple linear regression. Assumption tests, such as normality test, multicollinearity test, heteroscedasticity test, and linearity test, were performed. Moderated Regression Analysis (MRA) was used to test the moderating effect. The results indicate that the motivation, perception, knowledge, and attitude of Salon Deskhabeautylash consumers collectively influence purchasing decisions. Age strengthens the impact of motivation, perception, knowledge, and attitudes of Salon Deskhabeautylash consumers on purchasing decisions. Education level also strengthens the impact of motivation, perception, knowledge, and attitudes of Salon Deskhabeautylash consumers on purchasing decisions.